Low-Temperature Interdiffusion and Ordered Phase Formation in Au/Cu Nanocrystalline Thin Films at the Different Atmospheres - Tynkova, A.A.; Sidorenko, S.I.; Kotenko, I.E.; Svetchnikov, V.L.; Voloshko, S.M. (Металлофизика и новейшие технологии, 2014)
Interdiffusion processes in the polycrystalline Au (30 nm)/Cu (40 nm) thin films during annealing at 100—200°C for 15 and 30 min in a vacuum with different residual-atmosphere pressures of 10⁻² and 10⁻⁶ Pa and in an environment of hydrogen at a pressure of 5∙10² Pa are investigated.